Детермінанти нарощування конкурентоспроможності підприємств на засадах інноваційного розвитку - Трусова, Наталя Вікторівна; Трусова, Наталья Викторовна; Trusova, Natalia; Шершень, Н. В. (My University, 2020)
UK: У статті розкрито детермінанти підвищення конкурентоспроможності українських підприємств. Запропоновано модифікований системний підхід до оцінки рівня конкурентоспроможності з урахуванням універсального методу розширення функціональних властивостей його орієнтовних компонентів на інноваційній основі. Розроблено основу структурних перетворень рівня конкурентоспроможності через інтегрований підхід оцінки фінансових можливостей підприємств у системі виробничо-технологічного процесу та їх взаємозв'язок з факторами-симптомами, що мають прихований характер. EN: The article identifies the determinants of increasing the competitiveness of enterprises for innovative basis in Ukraine. A modified systematic approach to assessing the level of competitiveness of enterprises in the regions is proposed, taking into account the universal method of expanding functionality and indicative components of innovative development. The latent properties of the influence of the competitiveness of mechanical engineering enterprises in the system of production and technological process and their relationship with the factors-symptoms that have a latent nature are proved. The basis of structural transformations, which increase the competitiveness of enterprises in the regions a comprehensive approach to assessing their potential financial opportunities. Inventive capital is defined as an additional factor to strengthen competitiveness on an innovative basis for the development of enterprises in the regions. In addition, the expected results of settlement components of the competitiveness of enterprises in the regions of Ukraine have shown that in most cases their integrated indices are lower than the average standardized value. Incentives and disincentives for macroeconomic, industrial production, innovation, investment, foreign economic and financial development to determine the integrated level of increasing the competitiveness of enterprises in the long run provide regional empowerment and economic stability of economic entities. Under such conditions, there is a need to revise the current economic policy of the state, and, first of all, by increasing the autonomy of the regions regarding the differentiation of tax rates and benefits under the main types of taxes in order to ensure the financial stability.
Determinants of increasing competitiveness of enterprises on the basis of innovative development
Keywords: конкурентоспроможність; інноваційний розвиток; технології; товарно-матеріальний капітал; підприємство; competitiveness; innovative development; technologies; inventory capital; enterprise